Significações de funcionários da educação sobre a sua formação por meio do Profuncionário: o impacto em sua atividade profissional - Barbosa, Ana Paula (2018)
This research had the objective of recognizing the meanings of the Educational Employees of the public basic school, formed at the Instituto Federal de São Paulo, Campus São Paulo, regarding the education process in the Technical course of the School Secretary of the Profuncionário. The individuals for the first phase of the research were the 2014 class students and for the second phase two students chosen from this group. The procedures to produce information were: questionnaires sent to the class students and interviews with two students chosen based on the answers to the questionnaire, which were recorded and transcribed. The two participants were chosen considering the diversity between the responses, as one agreed with most of the statements while the other participant opposed them. The research is anchored on the assumptions of Socio-Historical Psychology, based on the theory of Vigotski, his followers and other contemporary authors. The data analysis was performed using the procedure called Nucleus of Meanings (AGUIAR; OZELLA, 2006, 2013; AGUIAR et al., 2015). The analysis reveals the need for initial and continuing education for the Educational employee; confirms the relevance of public policies for valuing this employee, such as education, minimum wage and career plan; infers, for the real recognition of the employee as an educator, the need for the educational employee to recognize himself as an educator, as well as the school community and society; indicates the course under analysis provided the understanding and respect for diversity, therefore improving the quality of the relationships. However, it points out the need for attention to affectivity in the planning and development of teaching-learning processes, especially in distance learning courses and to a better articulation between theory and practice, developing the praxis, in that it allows the reflection about practice